A Review of Central Vein Catheter for Hemodialysis: Insertion Sites and Techniques - Susanto, Jefri Pratama; Rifai, Achmad (Indonesian Journal of Kidney and Hypertension, 2024)
Chronic kidney disease (CKD) is a global epidemic, being increasingly prevalent in both developed and developing countries, including Indonesia. Hemodialysis (HD) is the primary renal replacement therapy, along with peritoneal dialysis and kidney transplantation. The effectiveness of HD relies on well-functioning vascular access, such as central vein catheters (CVCs). These catheters are classified by their duration of use: short-term, medium-term, and long-term. They are also distinguished by insertion type (central or peripheral), insertion site (jugular, subclavian, femoral), and number of lumens (single, double, triple). The preferred site for insertion is the internal jugular vein, followed by the femoral vein and the subclavian vein. Techniques for CVC insertion include the central approach, the posterior approach, and others. This article reviews the role of CVC for vascular access in HD. Specifically, various CVC insertion sites and techniques will be examined. The authors will also discuss the available research on the application of CVC as vascular access for HD in Indonesia.